Nanostructured TiO(2) cavitation agents for dual-modal sonophotocatalysis with pulsed ultrasound - Jonnalagadda, U.S. (Ultrason Sonochem, 2021)
Current sonochemical methods rely on spatially uncontrolled cavitation for radical species generation to promote chemical reactions. To improve radical generation, sonosensitizers have been demonstrated to be activated by cavitation-based light emission (sonoluminescence). Unfortunately, this process remains relatively inefficient compared to direct photocatalysis, due to the physical separation between cavitation event and sonosensitizing agent. In this study, we have synthesized nanostructured titanium dioxide particles to couple the source for cavitation within a photocatalytic site to create a sonophotocatalyst. In doing so, we demonstrate that site-controlled cavitation from the nanoparticles using pulsed ultrasound at reduced acoustic powers resulted in the sonochemical degradation methylene blue at rates nearly three orders of magnitude faster than other titanium dioxide-based nanoparticles by conventional methods. Sonochemical degradation was directly proportional to the measured cavitation produced by these sonophotocatalysts. Our work suggests that simple nanostructuring of current sonosensitizers to enable on-site cavitation greatly enhances sonochemical reaction rates.